1998
DOI: 10.3109/02841859809175485
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography in the Differential Diagnosis of Achilles Tendon Injuries and Related Disorders

Abstract: US can reliably be used for locating the Achilles tendon abnormality, estimating its severity, and determining most of the conditions requiring surgical intervention. However, US is not completely reliable for diagnosing peritendinitis and tendinitis, and it cannot be used to differentiate partial tendon ruptures from focal degenerative lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(103 citation statements)
references
References 15 publications
2
97
0
4
Order By: Relevance
“…US is valuable for finding the occurrence and location of tendon lesions, but it is unable to differentiate between partial tendon ruptures and focal degenerative areas (Åström et al, 1996(Åström et al, , Paavola et al, 1998. Sometimes mild to moderate changes can be found in both symptomatic and asymptomatic tendons and the changes that are seen are not always related to patients' symptoms (Paavola et al, 1998, Fredberg and Bolvig, 2002, Peers et al, 2003b. In a prospective study of the value of US and MRI in assessments of Achilles tendon disorders it was found that US identified abnormal morphology in 37 of 57 symptomatic tendons (65%) and normal morphology in 19 of 28 asymptomatic tendons (68%) (Khan et al, 2003b).…”
Section: Imaging Methodsmentioning
confidence: 99%
“…US is valuable for finding the occurrence and location of tendon lesions, but it is unable to differentiate between partial tendon ruptures and focal degenerative areas (Åström et al, 1996(Åström et al, , Paavola et al, 1998. Sometimes mild to moderate changes can be found in both symptomatic and asymptomatic tendons and the changes that are seen are not always related to patients' symptoms (Paavola et al, 1998, Fredberg and Bolvig, 2002, Peers et al, 2003b. In a prospective study of the value of US and MRI in assessments of Achilles tendon disorders it was found that US identified abnormal morphology in 37 of 57 symptomatic tendons (65%) and normal morphology in 19 of 28 asymptomatic tendons (68%) (Khan et al, 2003b).…”
Section: Imaging Methodsmentioning
confidence: 99%
“…Therefore, baseline US appearance is not able to predict clinical outcome. In Achilles tendinopathy, grey-scale ultrasonography is a costeffective method to examine the Achilles tendon [3,28,33,36]. As grey scale sonography is operator dependent, and relies on the detection of hypoechoic lesion and assessment of tendon thickening and widening, it was hoped that the addition of colour or power Doppler assessment would add objective evidence of pathology.…”
Section: Ultrasoundmentioning
confidence: 99%
“…Ultrasound shows partial ruptures of the Achilles tendon as wavy irregularities of the fibrillar echo pattern [33]. Focal hypoechogenic areas and thickening of the affected tendon segment are often seen [32]. Alfredson et al reported that the superficial dorsal tendon boundary also has an interruption and accompanying hyperperfusion can be visualized with power Doppler [33].…”
Section: Partial Rupturementioning
confidence: 99%
“…On the whole, the diagnosis of partial ruptures via ultrasound is limited with the differentiation from focal degenerative changes being particularly difficult [32]. Ultrasound shows partial ruptures of the Achilles tendon as wavy irregularities of the fibrillar echo pattern [33].…”
Section: Partial Rupturementioning
confidence: 99%
See 1 more Smart Citation